Implementation of Character Building by Teachers in Physical Education Subjects: A Sociological Analysis of Physical Education and Sports at SD Inpres Bertingkat Mamajang 2 - Taufiq Rahman; Muh. Bahrul Ulum; Muh. Adnan Hudain; Alimin Alwi (Asosiasi Dosen Muda Indonesia, 2025)
This study analyzes the implementation of character building by teachers in Physical Education (Penjas) at Mamajang 2 Elementary School through the perspective of the sociology of physical education and sports. The research focuses on four core values: discipline, collaboration, sportsmanship, and responsibility. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results indicate that Physical Education teachers play a crucial role in instilling character values through habituation, role modeling, and social interaction during learning. Discipline is reflected in students' adherence to rules and timetables, collaboration emerges in teamwork, sportsmanship is evident in honesty and accepting defeat, and responsibility is evident in students' concern for assignments and the learning environment. However, obstacles remain in the form of low student awareness and motivation, where character values have not been fully ingrained intrinsically. From the perspective of the sociology of education, this indicates a suboptimal moral socialization process. The study concludes that physical education has great potential as a means of building social character if teachers can consistently act as role models and facilitators of moral values.